An Approach to Prototyping Applications with Quantum Key Distribution - Tomkelski, Anderson; Freire, Marcus; Peixoto, Maycon; Souza, João; Silva, Valéria; Parizotto, Ricardo (Companion Proceedings of the Brazilian Symposium on Cybersecurity (SBSeg); 2025: Companion Proceedings of the 25th Brazilian Symposium on CybersecurityDO - 10.5753/sbseg_estendido.2025.14103, 2025)
Quantum Key Distribution (QKD) is a cryptographic technique based on the principles of quantum mechanics, aimed at securely establishing secret keys between parties. Despite significant advances in the field, there are still major challenges to its practical adoption, particularly in applications such as virtual private networks and end-to-end security. In this work, we propose an approach to prototype QKD-based applications by combining co-simulation techniques that integrate quantum simulators with network emulators. This integration enables prototyping in a flexible environment without requiring modifications to support a real QKD network. As a proof of concept, we implemented a private network application and evaluated its functionality.